Ten seconds of passive stretching reduces the maximum strength - Di Mauro, Henrique Scomparim; Junior, Roberto Moriggi; Dias, Sergio de Carvalho; Matos, Jaqueline Maria de; Urtado, Christiano Bertoldo (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: The flexibility and strength are the physical connected capabilities of the individual autonomy. When these are in adequate levels a considerable improvement in the quality of life of children, young, adults and older people has been noted. Nevertheless, for the development of these capabilities to be significant there must be an intervention of strength training (ST) and flexibility. However, according to recent evidence, there may be a possible interference between these two capabilities when performed in the same session, and the magnitude of this interference can be closely related to the duration and intensity of stretching. Objective: To assess whether the series of high intensity stretching (Flexing or stretching to its maximum amplitude) lasting ten seconds could negatively influence the strength generation. Method/Design: Were evaluated nine healthy volunteers practitioners of ST. Maximum strength was tested with and without a single stretching series, before the 1RM test (test re-test). Data were presented as mean ± standard deviation and the significance level was 0.05. Results: The results shows that the use of flexibility maneuver (FM) lasting 10 seconds in levels 8-10 visual analogue pain scale (classified as severe) was enough to depress at 3.15% (p = 0.021 95% CI = 0.42 to 4.01) maximum strength of subjects when compared to the method without MF. Conclusions: These data suggests that stretching may negatively interfere with the generation of maximum strength even in little time, leaving questionable practice for events that precede strength generation.